2017
DOI: 10.5812/ijpbs.7862
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Visual Attention Training Program on the Reduction of ADHD Symptoms in Preschool Children at Risk for ADHD in Isfahan: A Pilot Study

Abstract: Background: Attention deficit hyperactivity disorder (ADHD) symptoms are difficult to treat. As ADHD is naturally a disorder of attention and related executive functions, attention training (ATT) has been considered as a treatment for the disorder. Although there are few studies investigating the utility of ATT in the ADHD population, published studies provide support for ATT in reducing the symptoms of ADHD. Objectives:The aim of the current study was to examine the effects of training attention on ADHD sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…It is worth emphasizing that these findings are noteworthy in light of the fact that the small group intervention sessions were delivered by kindergarten teachers rather than research assistants, as was common in many previous intervention studies [14,27,28]. This is in accordance with the goals of the AK program, which not only strives to improve the cognitive skills of preschool children but also aims to enhance the professional development of teaching personnel.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is worth emphasizing that these findings are noteworthy in light of the fact that the small group intervention sessions were delivered by kindergarten teachers rather than research assistants, as was common in many previous intervention studies [14,27,28]. This is in accordance with the goals of the AK program, which not only strives to improve the cognitive skills of preschool children but also aims to enhance the professional development of teaching personnel.…”
Section: Discussionsupporting
confidence: 64%
“…These results are consistent with a growing body of research that has demonstrated the potential effectiveness of cognitive training for improving cognitive functioning in young children. For example, previous studies have found that cognitive training interventions can lead to improvements in cognitive functioning in children with ADHD [10,12,27,30], as well as in children with autism [31,32] and low socioeconomic backgrounds [14,34]. The current study adds to this literature by demonstrating the effectiveness of the AK intervention in a sample of kindergarten-aged children who were not diagnosed with any specific difficulties by a qualified clinician prior to the research and who did not come from a challenging socioeconomic background.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation